2015
DOI: 10.2118/171797-pa
|View full text |Cite
|
Sign up to set email alerts
|

Intercept Method—A Novel Technique To Correct Steady-State Relative Permeability Data for Capillary End Effects

Abstract: Summary In laboratory measurements of relative permeability, capillary discontinuities at sample ends give rise to capillary end effects (CEEs). End effects affect fluid flow and retention. If end-effect artifacts are not minimized by test design and data interpretation, relative permeability results may be significantly erroneous. This is a well-known issue in unsteady-state tests, but even steady-state relative permeability results are influenced by end-effect artifacts. This work describes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…A steady-state measurement of Q for a given Δ P / t would yield the permeability of the measurement. However, to account for capillary end effects and the pressure gauge’s zero offset, steady-state measurements were conducted at several pressure gradients. The Q versus Δ P / t data for the graphite plates of the present study were found to be linear and were corrected for a non-zero intercept by using a constant additive correction for Δ P (of ≅9 psi for all the specimens), which does not affect the slope of the curve (and therefore the permeability).…”
Section: Resultsmentioning
confidence: 99%
“…A steady-state measurement of Q for a given Δ P / t would yield the permeability of the measurement. However, to account for capillary end effects and the pressure gauge’s zero offset, steady-state measurements were conducted at several pressure gradients. The Q versus Δ P / t data for the graphite plates of the present study were found to be linear and were corrected for a non-zero intercept by using a constant additive correction for Δ P (of ≅9 psi for all the specimens), which does not affect the slope of the curve (and therefore the permeability).…”
Section: Resultsmentioning
confidence: 99%
“…At the end piece of the core, capillary pressure vanishes which yields to the accumulation of the wetting phase at the sample end . This phenomenon is called capillary end effect.…”
Section: Resultsmentioning
confidence: 99%
“…High capillary pressure in shales can cause a significant liquid hold-up at the outlet of the core, which is known as the capillary end effect (CEE). The CEE is also a dominant factor making relative permeability measurements incorrect and unreliable . Moghaddam and Jamiolahmady proposed a novel method to correct the CEE during steady-state relative permeability measurements for shales .…”
Section: Permeability Evaluationmentioning
confidence: 99%